Frequency of various dermatoses requiring histopathological evaluation for definitive diagnosis - Ehsan, Hina; Siddiqui, Saadiya; Aslam, Hira; Dustgir, Saima; Kazmi, Ramla; Altaf, Faria; Tariq, Hira; Aman, Shahbaz (Journal of Pakistan Association of Dermatologists, 2024)
Objectives: To determine the frequency (percentage) of various dermatoses in patients requiring biopsy for definitive diagnosis in a tertiary care hospital Methods: This descriptive Descriptive, cross-sectional study was conducted at department of dermatology, Services Hospital, Lahore.A total of 352 patients of both genders (who required biopsy for definitive diagnosis), 12 to 70 years of age were included. Patients with previous history of radiotherapy and chemotherapy were excluded. Biopsy was performed after taking consent from the patient or the guardian. Detailed examination of skin was performed for each patient, histopathological evaluation was done and recorded on predesigned proforma (attached). Frequency of various dermatoses were recorded as per-operational definition. Results: Frequency of eczema dermatitis was found in 115 (32.67%) patients, papulosquamous disorders like psoriasis in 27 (7.67%), Infectious skin diseases like leishmania in 22 (38.54%), drug reaction in 18 (5.11%) and others diagnosis in 170 (48.30%) patients. Conclusion: This study concluded that there should be early recognition and management of these disease in order to improve the quality of life of these particular patients.